Exploring the Interplay between Intercultural Competence, Student Motivation, and Psychological Adaptation in Multilingual Classrooms: Mechanisms and Educational Implications in Southeast Asia - Cemei Li; Linghong Tang; Ghozali Rusyid Affandi; Bingren Ma (P3I UMSurabaya, 2025)
In Southeast Asia’s culturally and linguistically diverse learning environments, multilingual classrooms provide a unique platform for nurturing intercultural competence, sustaining student motivation, and supporting psychological adaptation. This conceptual paper explores the dynamic interplay among these three constructs, drawing upon Byram’s model of intercultural communicative competence, self-determination theory, and positive psychology perspectives. It analyzes how the cognitive, affective, and behavioral dimensions of intercultural competence influence both intrinsic and extrinsic motivation, as well as students’ emotional well-being and adaptability in multilingual settings. Through an integrative review of existing research, the study develops a conceptual framework linking intercultural education and student psychology, aiming to promote a holistic understanding of learner development in multicultural contexts. The findings emphasize the importance of humanizing pedagogy, culturally responsive teaching, and socio-emotional support in enhancing motivation and psychological well-being. Finally, the paper offers practical implications for curriculum design, teacher training, and regional collaboration to foster inclusive and motivating multilingual learning environments across Southeast Asia.